IDENTIFIKASI PENGARUH AIR LINDI (LEACHATE) TERHADAP KUALITAS AIR DI SEKITAR TEMPAT PEMBUANGAN AKHIR (TPA) TANJUNG BELIT - Rahmi, Alfi; Edison, Bambang (Aptek, 2019)
Tanjung Belit landfill waste processing operations use a controlled landfil system, this is indicated by the presence of garbage collection ponds and leachate collection channels, but in the rainy season there is difficulty in accessing roads causing waste to be dumped outside the garbage collection pond, so that the TPA applies an open dumping system trash transported is immediately disposed of and stacked on land near the landfill. Waste deposits will produce a liquid known as lindi (leachate). This study aims to identify the effect of leachate from Tanjung Belit Landfill (TPA) on water quality around Tanjung Belit landfill. Samples were taken as many as 5 samples, namely leachate, monitoring well water and river water around the landfill where the parameters measured were pH, DO, TDS, BOD, COD, Nitrite, Sulphate and Chloride based on PP No. 82 of 2001 and KEPMEN LH No.51 of 1995 concerning Liquid Waste Quality Standards. The results of the analysis show that the leachate of Tanjung Belit landfill affects the quality of river water and monitoring well water around the Tanjung Belit landfill but is still classified as lightly polluted. The influence of distance on the quality of sunagi water and monitoring well water, namely the farther the distance, the less contamination in water.